Un diálogo ultra-breve como denuncia de la represión: Grotesco y metáfora en los microrrelatos de István Örkény y Ana María Shua - Gatti, Giuseppe (Verbum – Analecta Neolatina, 2014)
The central aim of our analysis consists of a comparative study about the literary representation of traumatic forms of violence that link themselves with the repression and the terror of State. We will concentrate our attention on two writers, the Hungarian playwright, novelist and writer István Örkény (1912–1979) and the Argentinian writer Ana Maria Shua (1951–): they share the same frequentness of a genre as the micro-fiction, a “narrative territory”, particularly fertile for the production of political allegories. The first object of reflection is the short story’s production of Örkény: especially, the stories “The new neighbor” and “The last bone of cherry”. Both tales belong to the book Egyperces novellák (1968), translated into the Spanish with the title of Cuentos de un minuto. The biography of Örkény reflects the way in which the trauma of violence and ostracism is re-elaborated across a writing style that appeals to the grotesque humor and to the irony. The second object of analysis is a selection of micro-fiction of Shua, from the books Temporada de fantasmas (2004) and Fenómenos de circo (2011). In both texts the fictional representation of the years of dictatorship that has characterized the recent history of the nations of the Cono Sur is constructed on a scheme that approaches the political history of Argentina from an allegoric fictionalization of authoritarianisms, censorship, violence and exile.